1973
DOI: 10.1192/bjp.122.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Ergotamine and Methysergide Abuse in Patients with Migraine

Abstract: Ergotamine preparations are extensively used in the treatment of migraine. Although not widely appreciated, there have been reports in the literature of ergotamine abuse, related to the development of tolerance and withdrawal headaches, which result in a steadily increasing consumption of the drug (Wolfson and Graham, 1949; Peters and Horton, 1951; Friedman et al., 1955). It is important clinically to recognize this condition, as ergotamine can have dangerous vascular side-effects (Byrne-Quinn, 1964; Cranley e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1973
1973
1999
1999

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…All 24 patients admitted that the ergotamine tartrate had been prescribed initially for treatment of acute migraine attacks only, but the effective dose had increased gradually until eventually 22 (92%) of the patients were taking the drug daily. This phenomenon agrees with the findings of other authors, 13,14,15,16 and has been explained by the development of tolerance by the patients to ergotamine. Wolff 17 has recommended that the weekly dose of ergotamine tartrate should not exceed 10 mg per week; however, ethical pharmaceutical companies manufacturing ergotamine tartrate preparations differ in their advice, variously recommending maximum weekly doses of 10, 12 and 24 mg. 18 Table 3 is a summary of the patients taking these recommended dosages.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…All 24 patients admitted that the ergotamine tartrate had been prescribed initially for treatment of acute migraine attacks only, but the effective dose had increased gradually until eventually 22 (92%) of the patients were taking the drug daily. This phenomenon agrees with the findings of other authors, 13,14,15,16 and has been explained by the development of tolerance by the patients to ergotamine. Wolff 17 has recommended that the weekly dose of ergotamine tartrate should not exceed 10 mg per week; however, ethical pharmaceutical companies manufacturing ergotamine tartrate preparations differ in their advice, variously recommending maximum weekly doses of 10, 12 and 24 mg. 18 Table 3 is a summary of the patients taking these recommended dosages.…”
Section: Discussionsupporting
confidence: 93%
“…8,9,10,11,12 However Peters and Horton, 13 Silverskiold,14 Friedman, Brazil and von Storch, 15 and more recently Lucas and Falkowski 16 have reported the occurrence of tolerance and increased frequency of headaches in some patients taking frequent doses of ergotamine tartrate. These same authors 13,14,15,16 have also reported that such patients can experience withdrawal headaches on discontinuance of the drug.A marked increase in the frequency of the headaches was noted by the 24 patients included in this study whilst taking regular doses of ergotamine tartrate. Withdrawal of the drug was associated with resolution of the symptoms.…”
mentioning
confidence: 90%
“…As reported in other studies, our patients showed all characteristics of physical and emotional dependence and had distinct psychological features with tendencies to overreact and depressive mood disturbances. 3,14 The pathophysiological mechanisms underlying drug-induced headaches and rebound headaches involve vascular and muscular mechanisms as well as disturbances of the endorphin system. 2,3,6,9,23 Drug-induced headaches were originally thought to be caused exclusively by the ergotamine components of pain relievers, 8,[10][11][12][13][14][15] several recent studies, however, have shown the occurrence of drug-induced headache without the use of ergotamine.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Originally, drug-induced headaches were thought to be caused by ergotamine components of pain relievers and therefore termed ergotamine headaches. 8,[10][11][12][13][14][15] Recent studies, however, have shown that a similar form of headache is caused by chronic use of analgesics without ergotamine components and therefore the terms analgesic-induced or drug-induced headaches should be preferred. 2,3,7,9,16 Drug-induced headaches are a common problem as 10-15% of the patients in headache clinics, and about 1% of the population in general suffer from this type of headache.…”
Section: Introductionmentioning
confidence: 99%
“…However, in later studies it was realized that also the chronic abuse of analgesics and other psycho tropic drugs could lead to drug-induced daily headache and that only consequent withdrawal therapy was able to reduce headache frequency and intensity (3)(4)(5)(6)(7)(8)(9)(10). In the first observations on chronic drug-induced headache, only ergotamine was assumed to cause this phenomenon (1, 2).…”
mentioning
confidence: 99%